Tuberculosis Related Ischemic Stroke : A Case Report - Pinzon, Rizaldy Taslim; Vidyatama, Veren Amoreta (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Tuberculosis (TB) is a widespread infectious disease caused by Mycobacterium Tubercle Bacilli. In 15-20 % cases of active pulmonary TB, infection spreads to extrapulmonary foci, including the nervous system complications. Ischemic stroke related tuberculosis without meningitis is rare. We report a 74-year-old female presented with rapid onset confusion, unconsciousness, and left hemiparesis. She had been recently diagnosed with active TB 3 months ago and treated with combination anti tuberculosis regiment. Her recent acute neurological manifestations began within 24 hours prior to admission in the hospital. The brain CT showed  middle cerebral artery territory infarction. The risk factors tracing found no significant abnormality. The only abnormal finding was high CRP. This report describes rare case of a patient with active TB and who presented with acute ischemic stroke.